Histopathological pattern in endometrial biopsies in reproductive age group and Post-menopausal women - Farah Fatima Abbas; Bukhari, Uzma; Khan, Nehad; Arshad, Fatima; Kamil, Saba (Journal of the Pakistan Medical Association, 2024)
Objective: To identify and analyse the different types and frequencies of morphological pattern in endometrial biopsies along with their associated diagnoses across different age groups. Method: The cross-sectional study was conducted at the Histopathology Section of the Dow Diagnostics Reference and Research Laboratory, Dow University Health Sciences, Karachi, from October 2022 to October 2023. Data was obtained from pre-existing medical record of samples of endometrial biopsies. Open Epi sample size calculator is used for the estimation of sample size. The patients were divided into two aged-based groups; reproductive age 45 years in group 1 and post-menopause age 46 years in group 2. The histological diagnosis was made by a consultant histopathologist. Result: Of the 430 endometrial biopsies 222(51.6%) were in group 1 and 208(48.4%) were in group 2. In both groups, the most common finding was polyps 271(63%). Malignant changes were found in 12(5.7%) group 2 cases compared to 4(1.8%) group 1 cases. Conclusion: The most common endometrial lesion in both age groups was endometrial polyp. Malignant changes were seen more in postmenopausal women compared to those in the reproductive age group. Key Words: Endometrial hyperplasia, Heavy menstrual bleeding, Postmenopausal period, Abnormal uterine bleeding, Dysfunctional uterine bleeding, Endometrial cancer.